Haematological manifestations in patients with severe acute respiratory syndrome: retrospective analysis. Issue 7403 (19th June 2003) - Wong, Raymond S M; Wu, Alan; To, K F; Lee, Nelson; Lam, Christopher W K; Wong, C K; Chan, Paul K S; Ng, Margaret H L; Yu, L M; Hui, David S; Tam, John S; Cheng, Gregory; et al.
Abstract: Objectives To evaluate the haematological findings of patients with severe acute respiratory syndrome (SARS). Design Analysis of the demographic, clinical, and laboratory characteristics of patients with SARS. Setting Prince of Wales Hospital, Hong Kong. Subjects All patients with a diagnosis of SARS between 11 March and 29 March 2003 who had no pre-existing haematological disorders. Main outcome measures Clinical end points included the need for intensive care and death. Univariate and multivariate analyses were performed to examine factors associated with adverse outcome. Results 64 male and 93 female patients were included in this study. The most common findings included lymphopenia in 153 (98%) of the 157 patients, neutrophilia in 129 (82%), thrombocytopenia in 87 patients (55%), followed by thrombocytosis in 77 (49%), and isolated prolonged activated partial thromboplastin time in 96 patients (63%). The haemoglobin count dropped by more than 20 g/l from baseline in 95 (61%) patients. Four patients (2.5%) developed disseminated intravascular coagulation. Lymphopenia was shown in haemato-lymphoid organs at postmortem examination. Multivariate analysis showed that advanced age and a high concentration of lactate dehydrogenase at presentation were independent predictors of an adverse outcome. Subsets of peripheral blood lymphocytes were analysed in 31 patients. The counts of CD4 positive and CD8 positive T cells fell early in the course of illness. Low counts of CD4 and CD8 cells at presentation were associated with adverse outcomes. Conclusions Abnormal haematological variables were common among patients with SARS. Lymphopenia and the depletion of T lymphocyte subsets may be associated with disease activity.